Studies on Ruthenium(III) Complexes of Amide Group Containing Ligands - Raju, K.; Dayakar, G. (Asian Journal of Chemistry, 2010)
Complexes of Ru(III) with 3-phenyl-4-benzamidoethenyl- b-carboxy-5-isoxazolone, b-(3-methyl-4-isoxazolylamido-5- styryl)-benzoic acid, b-(3-methyl-4-isoxazolylamido-5- styryl)acrylic acid, b-(3-methyl-4-isoxazolylamido-5- styryl)propionic acid, b-(5-methyl-3-isoxazolylamido)benzoic acid, b-(5-methyl-3-isoxazolylamido)acrylic acid and b-(5- methyl-3-isoxazolylamido)propionic acid have been synthesized and characterised by elemental analysis, conductance, thermal, magnetic, infrared and electronic spectral data. The above data suggest that the complexes are octahedral in geometry.